The arcade of Struthers: an anatomical study and clinical implications - Edie Benedito Caetano; João José Sabongi Neto; Luiz Angelo Vieira; Maurício Ferreira Caetano (Revista Brasileira de Ortopedia)
ABSTRACT OBJECTIVE: To determine the frequency and features of the arcade of Struthers, and to assess its clinical implication in ulnar nerve compression. METHOD: Forty arms from 26 cadaver specimens were dissected in the Anatomy Laboratory of this institution. The extension of the arcade, distance from the medial epicondyle, and relation with ulnar nerve were recorded. RESULTS: The arcade of Struthers was identified in 40 dissected arms (100%). In 29 (72.5%) the ulnar nerve was covered by a muscular arcade, in nine (22.5%) by an aponeurotic arcade, and in two (5%) the arcade was beneath the ulnar nerve. The extension of the arcade ranged from 3.0 to 7.5 cm, and the distance from the medial epicondyle ranged from 2.5 to 7.0 cm. CONCLUSION: The arcade of Struthers is a musculoaponeurotic canal that represents an important site of entrapment or compression of the ulnar nerve. The arcade, the intermuscular septum, and the internal brachial ligament should be released in patients submitted to ulnar nerve anterior transposition surgery.